LABOR POTENTIAL OF FORMATION AND DEVELOPMENT OF THE SERVICES SECTOR IN THE REGIONS OF THE RUSSIAN FEDERATION - Morozov, Vladimir; Khavanova, Natalya; Rozhdestvenskaya, Irina (Revista Inclusiones, 2020)
The social life and production processes become more complicated in the modern conditions, which is accompanied by further specialization of activities. The intensified international competition leads to tougher competition in national labor markets. There is a growing instability of many enterprises and thereby of the existing job system. New forms of labor organization are emerging, focused on greater flexibility in hiring forms (including the wider use of part-time employment). Inequality in wages is increasing, the role of trade unions is decreasing, and a noticeable feminization of jobs is observed in developed countries. As such, it can be stated that a fundamental restructuring process is taking place in the labor market.